As quest??es ??ticas da propaganda : um estudo com profissionais de ag??ncias de propaganda - Telles, Cec??lia Caraver Prado (2007)
The aim of this job is to verify what the advertisers think, how they feel and how is their behaviour about the ethic questions of advertising. The marketing literature shows that there is a wide range of ethic and legal questions in the marketing and promotion set of actions involving a firm. In a market economy in order to support the consumers decision process with information they learn to trust in advertising and another promotional tools. However, if the consumer s information wouldn t be true or would be deceptive, the advertising won t be carrying out its basic function. These research objectives have determined the conditions for an exploratory and qualitative study, and the use of a nonprobabilistic sample of 30 interviews with advertisers from S??o Paulo city. The Social Representations Theory was chosen as a theoretical frame to understand the phenomenon in question. The Social Representations Theory says a collective speech could be found in theindividual minds. In this theory both the individual level and the social level are evaluated. The individual evaluation level consists of perceptions, memories, attitudes, intentions, thoughts, emotions, affects, behaviours and also believes shared by individuals and common to the set of interviewers. The social level evaluation consists of facts that appear to individual as a societies characteristics, cultures, groups, subcultures, social classes, subgroups. This study checked that the advertisers interviewed know what ethic means, its reach and characteristics. They also know that an advertising ethic behaviour is reached through a responsible and ethic business advertising management, expressed in the message, in clients relationship, in suppliers or partners relationship, in competition situations, leading the internal team, and the colleagues and leadership granted treatment. The main advertising ethic questions mentioned were: true presentation (the arguments used must be proved), plagiarism, children advertising, client relationship, human being disrespect as prejudice, injure feelings, discrimination or despising, tobacco advertising, alcoholic beverage advertising and weapon advertising. The advertisers interviewed in this job are conscious of the need in having an ethical behaviour in general, in all life s moments, as in the society, as in the professional activity, and they also know the advertising reach and its limitations, as ordered in the Advertising Self Regulation Code.